Current surgical guidelines. - Jibawi, Abdullah; Baguneid, Mohamed; Bhowmick, Arnab ([Oxford] : Oxford University Press, 2018)
This handbook summarises all the available UK-oriented surgical guidelines. It contains diagrams, algorithms, audit tools and user-friendly statistics to make surgical practice an enjoyable well-informed learning experience.
This edition previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 6, 2018).
Keywords: Surgery